(untitled) (Research, Society and Development, 2025)
Objective: To analyze the situation of women in situations of social vulnerability, exploring its multiple dimensions and assessing its impact on access to primary health care. Method: This is a reflective analysis study, based on a bibliographic review, carried out on scientific articles, books and book chapters during the period 2019-2024 in Portuguese, Spanish and English, in the following databases: Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Health Sciences Literature and SciELO Virtual Library. Results and discussion: The analysis reveals that socio-economic and cultural inequalities in Brazil affect women’s access to health services, especially in rural areas. Conclusion: The results show the complexity of the reality of women in situations of social vulnerability.